RISK-BASED ROAD RESOURCE ALLOCATION USING SDI AND ADT DATA - Sulistyowati; Diah Aryati Puji Lestari; Son Haji; Sutik (Jurnal Teknik Sipil, 2026)
Safety is the most important aspect of a road to consider. Road safety means the road is in good condition for a vehicle to pass on. Maintenance and reconstruction are the two means that should be performed to preserve road performance and safety. Bina Marga Semarang, as the road administrator, uses Surface Distress Index (SDI) data to determine the appropriate maintenance/reconstruction (M/R) work on a road within the road network in Semarang. The SDI method gives a score based on each road segment condition; the lower the score, the better the road condition, which means the less road damage. This research aimed to allocate resources based on the risk inherent in each road section. SDI in 2024 and Average Daily Traffic (ADT) data in 2023 were used to quantify the risk magnitude of each road section in the Kecamatan Tugu, Semarang road network. The maintenance/reconstruction cost of each segment was also calculated to determine the road M/R cost. Road segments were then ranked based on the risk magnitude and M/R cost. The result showed that JL. Stasiun Jrakah was the riskiest road, but held the 7th position in M/R cost.